The influence of growth stage on the nutritional value of Panicum maximum (cv. Gatton) and Digitaria eriantha spp. eriantha silage for sheep - Van Niekerk, Willem A. (University of Pretoria, 2013)
Dissertation (MSc Agric (Animal Nutrition))--University of Pretoria, 2006.